If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 15 + -6x = 8 + -1(7x + 2) Reorder the terms: 15 + 2x + -6x = 8 + -1(7x + 2) Combine like terms: 2x + -6x = -4x 15 + -4x = 8 + -1(7x + 2) Reorder the terms: 15 + -4x = 8 + -1(2 + 7x) 15 + -4x = 8 + (2 * -1 + 7x * -1) 15 + -4x = 8 + (-2 + -7x) Combine like terms: 8 + -2 = 6 15 + -4x = 6 + -7x Solving 15 + -4x = 6 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 15 + -4x + 7x = 6 + -7x + 7x Combine like terms: -4x + 7x = 3x 15 + 3x = 6 + -7x + 7x Combine like terms: -7x + 7x = 0 15 + 3x = 6 + 0 15 + 3x = 6 Add '-15' to each side of the equation. 15 + -15 + 3x = 6 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = 6 + -15 3x = 6 + -15 Combine like terms: 6 + -15 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| x^2+(-0.429x+15)*(-0.429x+15)-12x-16(-0.429x+15)+71=0 | | 5.50x+8y=90 | | 2r^2-3r-2=0 | | (2w+15)(2w+10)=250 | | x(2x+1)=10 | | -8-8n=1-5n | | 20x-10x-5y+5y=15 | | 11x-3=4(3x-4) | | 68=4LW+2wh | | -11+8n=n-4 | | s^2+35=0 | | 3x+22=12x-7 | | 0.5r+6=3-3r | | 3v+8=8+2v+1v | | 6x^2-18x+13=0 | | 3x=2x+p | | 2s^2=s+6 | | -4m-13m= | | 9(a+14)+8(b-16)=0 | | r^2+15=-8r | | 0.333333333+0.666666667m=0.666666667m-0.666666667 | | 4+4p=4p+7-1 | | 8x^2-512=0 | | 5*(3+2x)+80=2*(5x-1) | | 14-9x=54-44x | | -6(y+8)=-6y+12 | | 21x+4x-8x= | | 14-9x=54-4x | | 3(y+4)+3=24 | | 7.9y+8.4-2.04y=0 | | 7(2x+4)=2-(30-x) | | 1=lnx |